The Employee Performance Perspective Influenced By Supervision, Commitment, and Work Discipline at The Human Resource Development Agency of South Sulawesi Province - Nurlinda Hijrah; Andi Jam’an; Samsul Rizal; Akhmad Akhmad; Muh. Ikram Idrus (Eduvest - Journal of Universal Studies, 2024)
This study aims at determining and analyzing the influence of supervision, work commitment and work discipline on employee performance at the South Sulawesi Province Human Resources Development Agency (BPSDM) South Sulawesi Province. The research method used was quantitative research with data collection technique through survey using questionnaires with the sample size were 102 respondents.  The data obtained was anlyzed using Multiple Linear Regression to determine the correlation between variables using the SPSS V.24 application. The results of the research show that Supervision brought influence but it was not significant on employee performance, while commitment and work discipline  got significant influence on employee performance, with an overall confidence level was 95%.